ANALISA KINERJA KEUANGAN PT. MATAHARI DEPARTEMENT STORE TBK DENGAN PT. RAMAYANA LESTARI SENTOSA - Sulistianto, R. Hario; Haikal, Fahri (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
This study entitled "Financial Performance Analysis of PT. Matahari Department Store Tbk With PT. Ramayana Lestari Sentosa Tbk (2018-2022 Period)" is motivated by the increasing number of people who start shopping online rather than shopping directly in stores, so the author wants to see what the financial performance is like in conventional companies in this case PT. Matahari Department Store Tbk and PT. Ramayana Lestari Sentosa Tbk. The purpose of this study is to analyze the differences in performance between PT. Matahari Department Store Tbk and PT. Ramayana Lestari Sentosa Tbk using the ratio analysis method and bankruptcy analysis (Altman Z-Score). The sample in this study were companies listed on the Indonesia Stock Exchange in the non-primary consumer goods sector (E), Retail Trade Sub-sector (E7), Department Store Industry (E73), Department Store Sub-industry (E731), Department store sub-industry in the period 2018-2022. This study uses a descriptive quantitative method, by analyzing the financial statements of PT. Matahari Department Store Tbk and PT. Ramayana Lestari Sentosa Tbk. The results of this study indicate that both companies have good financial performance, with PT. Matahari Department Store Tbk tending to be better seen in the activity ratio and profitability ratio.